Absence of the lectin-like domain of thrombomodulin reduces HSV-1 lethality of mice with increased microglia responses - Meng-Shan Tsai; Li-Chiu Wang; Hua-Lin Wu; Shun-Fen Tzeng; Edward M. Conway; Sheng-Min Hsu; Shun-Hua Chen (Journal of Neuroinflammation, 2022)
Abstract Background Herpes simplex virus 1 (HSV-1) can induce fatal encephalitis. Cellular factors regulate the host immunity to affect the severity of HSV-1 encephalitis. Recent reports focus on the significance of thrombomodulin (TM), especially the domain 1, lectin-like domain (TM-LeD), which modulates the immune responses to bacterial infections and toxins and various diseases in murine models. Few studies have investigated the importance of TM-LeD in viral infections, which are also regulated by the host immunity. Methods In vivo studies comparing wild-type and TM-LeD knockout mice were performed to determine the role of TM-LeD on HSV-1 lethality. In vitro studies using brain microglia cultured from mice or a human microglia cell line to investigate whether and how TM-LeD affects microglia to reduce HSV-1 replication in brain neurons cultured from mice or in a human neuronal cell line. Results Absence of TM-LeD decreased the mortality, tissue viral loads, and brain neuron apoptosis of HSV-1-infected mice with increases in the number, proliferation, and phagocytic activity of brain microglia. Moreover, TM-LeD deficiency enhanced the phagocytic activity of brain microglia cultured from mice or of a human microglia cell line. Co-culture of mouse primary brain microglia and neurons or human microglia and neuronal cell lines revealed that TM-LeD deficiency augmented the capacity of microglia to reduce HSV-1 replication in neurons. Conclusions Overall, TM-LeD suppresses microglia responses to enhance HSV-1 infection.